The Health Service Quality Model: State Primary Care Perspective (Survey, Evaluation, and Strategy) - Herni Justiana Astuti; Suryo Budi Santoso; Devita Elsanti (CV. Creative Tugu Pena, 2025)
This Quality of basic health services remains a persistent global and national policy concern, particularly at the primary-care level where community health centers (Puskesmas) serve as the frontline of universal health coverage. This study analyzes the quality of government-owned primary health services through three complementary perspectives: survey, evaluation, and strategy. Previous studies on Puskesmas service quality have generally been limited to a single analytical approach and rarely provide actionable strategic recommendations for both health centers and patients. Respondents consisted of 103 BPJS outpatients, 97 non-BPJS outpatients from eight Puskesmas in Banyumas Regency, and eight heads of Puskesmas. The survey dimension applies the Community Satisfaction Index (CSI), the evaluation dimension applies Importance Performance Analysis (IPA), and the strategy dimension applies the Service Quality Gap Model. The CSI results indicate that service quality for both BPJS and non-BPJS patients is categorized as “good,” although conformity levels remain below 100 percent. IPA findings show no service element in Quadrant A for BPJS patients, whereas complaint, suggestion, and feedback handling emerge as the top priority for non-BPJS patients. The Gap Model reveals perception–expectation gaps in requirements and cost/tariff for BPJS patients, while gaps for non-BPJS patients extend to requirements, completion duration, cost/tariff, staff competence, staff behavior, and complaint handling. These findings imply that Puskesmas management should strengthen patient feedback channels and prioritize improvements in staff competence and complaint-handling mechanisms to enhance overall service quality.